The Relationship Between Academic Procrastination and Sleep Quality of Students of Medical Study Program, Faculty of Medicine, Diponegoro University During the COVID-19 Pandemic - Athaya Zayyan Pusparini; Fanti Saktini; Hang Gunawan Asikin; Tanjung Ayu Sumekar (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2022)
Background: The COVID-19 pandemic requires the government to take policies by establishing online learning. Online learning has significantly provided changes to students' daily activities, thus resulting in academic procrastination. Academic procrastination is defined as an act of postponing academic activities that may lead to decreased academic performance, increased physical, emotional, mental problems, and unhealthy sleep patterns. Sleep is referred to as a crucial activity of daily routines, and poor sleep quality may contribute to negative impacts on academic success. Aim: To evaluate the relationship between procrastination and sleep quality for students of the Medical Study Program, Faculty of Medicine, Diponegoro University, during the COVID-19 pandemic. Method: This research used a cross-sectional design. Subsequently, 84 active students of the Faculty of Medicine, Diponegoro University, Class of 2020, were found to meet the research criteria, agreed to the informed consent, and filled out the complete questionnaire. The statistical test used was Spearman's test analysis. Results: Referring to the results obtained, there was no significant relationship between academic procrastination and sleep quality for students during the COVID-19 pandemic. Moreover, 39 (46.4%) students were identified as having a high level of academic procrastination. Meanwhile, the majority of students with poor sleep quality during the COVID-19 pandemic was amounted to 52 (61.9%). Conclusion: There was no significant relationship between academic procrastination and sleep quality for students of the Medical Study Program, Faculty of Medicine, Diponegoro University, during the COVID-19 pandemic.